A genre - based analysis of academic exercise introductions in the B.Ed TESL program, UiTM, Malaysia / Syarina Mahmood - Mahmood, Syarina (2012)
There have been a number of studies in recent years of written academic genres and they have highlighted the importance of genre analysis in the structure of student writing. The study utilised a content document analysis method to investigate the use of rhetorical moves in the introductions to academic exercise written by B.ed TESL students in Universiti Teknologi MARA (“UiTM”) Shah Alam, Selangor, Malaysia. The thesis describes how genre analysis was used to analyse the academic exercise introductions of a corpus composed of 30 texts written in English by Malaysian writers. The analysis reveals that the rhetorical patterns and some moves proposed by Swales in his Open a Research Option model are found in introductions even though not in sequence orders. Another significant finding is that the Malaysian writers did not summarise their finding in the introduction sections compared to Anglo-American writers. The objectives of this analysis are to verify whether the rhetorical patterns of organisation and the moves found in introductions coincide with those proposed by Swales (1993) in his study of research articles introductions. Besides analyzing the CARS model by Swales (1993), it also identifies the alternative model of Open a Research Option (OARO) in the introductions. The finding was different from those for English RA introductions because Malaysian and Anglo-American writers have different backgrounds and environments due to the social-cultural aspects with also reflect the organisation of discourse and rhetoric. Malaysian writers do not like to comment on other peoples’ works compared to cultures who like to give and accept criticism. To conclude the introduction section of their writing, Malaysian writers preferred referring to the consequences of their research. In general, the rhetorical moves and steps were employed in academic exercise introduction sections were less often used in CARS compared to OARO.